Importancia de la proactividad y su incidencia en el ámbito laboral de las secretarias del Gobierno Autónomo Descentralizado Municipal del Cantón Caluma en el año 2021 - Suárez Orta, Silvana Stefania (2022)
The main focus of the case study is to describe, investigate and analyze the topic: Importance of proactivity and its incidence in the work environment of the secretaries of the Municipal Decentralized Autonomous Government of the canton Caluma in the year 2021,study project that has as a priority to make proposals regarding the solutions that can be given within the GAD for such reason the deductive method was used, due to the fact that it starts from the general to the particular, This method allows us to obtain data of high value that gives us the possibility of concluding significantly, or as mentioned above, a qualitative analysis was applied, which allows us to know or describe qualities of the personnel or variables immersed in the study, or in other words, its approach is to understand phenomena and explore them from the point of view of the collaborators in a natural environment and in relation to their context, As an instrument to collect information we had the survey which was applied to a sample size of 10 people corresponding to the total number of secretaries of the GAD, after this process we proceeded to tabulate the information obtained in order to know in which question the secretaries have generalized confusion, resulting in the lack of knowledge of evaluation processes, this clearly indicates that the GAD does not perform such evaluation to the work exercise carried out by the secretaries, one of the most important results is that 100% of secretaries consider that proactivity has an impact on the work exercise.